Consensus from an expert panel on how to identify and support food insecurity during pregnancy: A modified Delphi study - Fiona H. McKay; Julia Zinga; Paige van der Pligt (BMC, 2022)
Abstract Background Food insecurity and hunger during pregnancy have significant implications for the health of the mother and baby. Assisting clinicians when they encounter women who are experiencing hunger or food insecurity during their pregnancy will increase the opportunity for better birth and pregnancy outcomes. At present there are no guidelines for Australian clinicians on how to do this. Methods This study uses a modified Delphi technique, allowing diverse participation in the process, to create consensus on the ways to address and respond to food insecurity during pregnancy. This modified Delphi collected data via two rounds of consensus. The opinions collected from the first round were thematically categorised and grouped. The topics were integrated into the survey for the second round and circulated to participants. During the second round, priorities were scored by giving five points to the topic considered most important, and one point to the least important. Results Through two rounds of consultation, the panel achieved consensus on how to identify food insecurity during pregnancy, with some clear items of consensus related to interventions that could be implemented to address food insecurity during pregnancy. Experts achieved consensus on items that have importance at the institution and policy level, as well as services that exist in the community. The consensus across the spectrum of opportunities for assistance, from the clinical, to community-provided assistance, and on to government policy and practice demonstrate the complexity of this issue, and the multipronged approach that will be required to address it. Conclusion This is the first time such a consultation with experts on hunger and food insecurity during pregnancy has been conducted in Australia. Items that achieved consensus and the importance of the issue suggest several ways forward when working with pregnant women who are hungry and/or food insecure.